Intralesional measles, mumps and rubella vaccine versus formic acid puncture in the treatment of common warts: A prospective randomised study - Myfanwy J D'Souza; Ganesh K Hundi; Sukumar Dandekeri; Jyothi Jayaraman (Wolters Kluwer Medknow Publications, 2023)
Context: Many therapeutic modalities have been reported for the treatment of warts: a common bothersome condition; however, no single treatment is completely effective. Aims: This study aimed to evaluate the efficacy and safety of intralesional injection of measles, mumps and rubella (MMR) vaccine and to compare its efficacy with 85% formic acid puncture for common warts. Settings and Design: This was a prospective comparative study. Methods and Material: A total of 60 patients, divided into two groups, were included in the study. Group A received an intralesional MMR vaccine of 0.3 ml per lesion, and group B received 85% formic acid puncture into each lesion with a maximum of 10 warts treated in each case. Five sessions were conducted every 2 weeks in each case with a follow-up period of 3 months to check for recurrence. Statistical Analysis Used: The Chi-square test, Fisher's test and t-test were used for statistical analysis. A P-value <0.05 was considered statistically significant. Results: In group A, the complete response was observed in 62.5%, partial response in 8% and no response in 4.1% of patients. In group B, the complete response was observed in 31.8%, partial response in 63.6% and no response in 4.5% of patients. The difference in cure rates was found to be statistically significant with a P value of 0.031. No recurrence was observed in both groups in the follow-up period. Conclusions: Immunotherapy by intralesional MMR vaccine is a simple, well-tolerated, effective and cost-benefit modality for the treatment of warts and showed a statistically significant cure rate than formic acid therapy.